Rapid effective dose calculation for raster-scanning 4He ion therapy with the modified microdosimetric kinetic model (mMKM). (January 2021) - Kopp, B.; Mein, S.; Tessonnier, T.; Besuglow, J.; Harrabi, S.; Heim, E.; Abdollahi, A.; Haberer, T.; Debus, J.; Mairani, A.
Highlights: Establish 4 He beam mixed radiation field spectra for the 1st clinical TPS with active beam delivery. Fast GPU-accelerated mMKM – based RBE predications in 4 He ion beam therapy. Sensitivity study towards patient treatment with 4 He ion beam therapy. Abstract: Purpose: To develop and verify effective dose (DRBE ) calculation in 4 He ion beam therapy based on the modified microdosimetric kinetic model (mMKM) and evaluate the bio-sensitivity of mMKM-based plans to clinical parameters using a fast analytical dose engine. Methods: Mixed radiation field particle spectra (MRFS) databases have been generated with Monte-Carlo (MC) simulations for 4 He-ion beams. Relative biological effectiveness (RBE) and DRBE calculation using MRFS were established within a fast analytical engine. Spread-out Bragg-Peaks (SOBPs) in water were optimized for two dose levels and two tissue types with photon linear-quadratic model parameters αph, βph, and (α/β)ph to verify MRFS-derived database implementation against computations with MC-generated mixed-field α and β databases. Bio-sensitivity of the SOBPs was investigated by varying absolute values of βph, while keeping (α/β)ph constant. Additionally, dose, dose-averaged linear energy transfer, and bio-sensitivity were investigated for two patient cases. Results: Using MRFS-derived databases, dose differences ≲2% in the plateau and SOBP are observed compared to computations with MC-generated databases. Bio-sensitivity studies show larger deviations when altering the absolute βph value, with maximum D50% changes of 5%, with similar results for patient cases. Bio-sensitivity analysis indicates a greater impact on DRBE varying (α/β)ph than βph in mMKM. Conclusions: The MRSF approach yielded negligible differences in the target and small differences in the plateau compared to MC-generated databases. The presented analyses provide guidance for proper implementation of RBE-weighted 4 He ion dose prescription and planning with mMKM. The MRFS-DRBE calculation approach using mMKM will be implemented in a clinical treatment planning system.